1995
DOI: 10.1071/rd9950871
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and concepts in the cryopreservation of spermatozoa and the assessment of their post-thawing function

Abstract: New research on the cooling and cryopreservation of mammalian spermatozoa is reviewed in the context of the older literature. Cryoinjury to a variety of cell organelles is regarded as being due to the two major stresses of cryopreservation, i.e., the change in temperature, and the formation and dissolution of ice and its consequences. Since the cryopreservation process involves departure of the cells from and return to body temperature, both cold shock and warm shock are included as potential stresses to be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
479
2
151

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 915 publications
(646 citation statements)
references
References 94 publications
(133 reference statements)
14
479
2
151
Order By: Relevance
“…Pugliesi et al (2012) não observaram diferenças (P>0,05) quanto à motilidade progressiva durante o TTR, nos tempos de 0, 20, 40, 60 e 90 minutos em Mangalarga Marchador, contudo observaram perda de 18,4% da motilidade progressiva do sêmen descongelado ao tempo 0 do TTR em comparação ao sêmen fresco (67,7% vs 49,3%), enquanto que Furst (2006) observou perdas de 28,6% no T0 e ao final do TTR (90 minutos) este valor não ultrapassou 50,0%. A diminuição na integridade funcional da membrana plasmá-tica do espermatozoide após o TTR parece ocorrer devido aos danos causados pelo processo de criopreservação nas estruturas e organelas envolvidas na movimentação espermática (Watson 1995).…”
Section: Discussionunclassified
“…Pugliesi et al (2012) não observaram diferenças (P>0,05) quanto à motilidade progressiva durante o TTR, nos tempos de 0, 20, 40, 60 e 90 minutos em Mangalarga Marchador, contudo observaram perda de 18,4% da motilidade progressiva do sêmen descongelado ao tempo 0 do TTR em comparação ao sêmen fresco (67,7% vs 49,3%), enquanto que Furst (2006) observou perdas de 28,6% no T0 e ao final do TTR (90 minutos) este valor não ultrapassou 50,0%. A diminuição na integridade funcional da membrana plasmá-tica do espermatozoide após o TTR parece ocorrer devido aos danos causados pelo processo de criopreservação nas estruturas e organelas envolvidas na movimentação espermática (Watson 1995).…”
Section: Discussionunclassified
“…One possible explanation for our findings is that human spermatozoa is very permeable to glycerol [16], so this changes in cellular volume occurs in a short period, while the more impermeable membrane of the stallion spermatozoa makes this process to occur much more slowly and thus causing more damage. It has been hypothesized that the actin cytoskeleton is damaged during cryopreservation [35,36] and indirect evidence have been described in ram spermatozoa [37]. In order to further determine if glycerol may damage the sperm cytoskeleton the percentage of F actin was evaluated.…”
Section: -Discussionmentioning
confidence: 99%
“…The reasons for the variation in the susceptibility of spermatozoa to injury could lie in differences that have been identified in sperm quality such as membrane integrity and functionality, adenosine triphosphate (ATP) content, and mitochondrial functionality [21]. Recent studies suggest that there is a genetic basis for variation in thawed sperm quality, and also suggest that molecular technologies could identify markers linked to genes influencing this variation [24,25]. In the present study, gonadosomatic index and body condition factor were recorded and are suggested as indicators for evaluating zebrafish sperm quality for cryopreservation.…”
Section: Discussionmentioning
confidence: 99%